Viruses and virus diseases of maize in tropical Africa - Thottappilly, G.; Rossel, H.W.; Bosque Pérez, N.A. (1995)
Seven viruses are known on maize in tropical Africa, however, information is still scanty. MSV is widely distributed in sub-Saharan Africa; other viruses are less widely spread or only of local importance. Information on viruses and virus diseases is useful to plant breeders in setting priorities. Resistance breeding is the most practical solution for control.